PENGEMBANGAN KURIKULUM PROGRAM KEAHLIAN TEKNIK OTOMOTIF BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PENGUATAN HARD SKILLS DAN SOFT SKILLS SISWA SMK PONTREN DARUSSALAM DEMAK - Ahsin Takiyudin; Popi Suranti; Sabar Narimo; Sumardjoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid expansion of automotive technology requires vocational schools to design curricula that are adaptive and aligned with modern industry needs. This study examines the development of a CTL-based Automotive Engineering curriculum to enhance students' hard skills and soft skills, particularly at SMK Pontren Darussalam. This qualitative study employs a literature review of national and international publications from 2021 to 2025, analyzed using thematic analysis. The results show that the implementation of CTL strengthens technical competencies through contextual learning, hands-on workshop activities, and the use of digital diagnostic tools. Meanwhile, soft skills are improved through collaborative tasks, technical communication, reflection, and teaching factory activities. Overall, CTL is highly effective for developing vocational students’ competencies and preparing them for the workforce.